Can Fintechs Stabilize the Financial Sector? - Martin Windl (ZBW - Leibniz Information Centre for Economics, 2020)
The growing popularity of fintechs has led the Financial Stability Board (FSB) to publish considerations about the effects of this emerging industry on stability and efficiency in the financial sector. Against this background, this paper compares the effects of competition and collaboration between banks and fintechs on stability and efficiency. Using a partial equilibrium model and a general equilibrium model with moral hazard between investors and the financial sector based on Martinez-Miera and Repullo (2017), this paper shows that cooperation between banks and fintechs increases stability and efficiency compared to the case of a competitive equilibrium. The findings are robust to changes in bargaining power within the financial sector but depend critically on contestable loan markets.
Keywords: G21; G23; G28; 330; fintech; bigtech; financial stability; general equilibrium